Skin Darkening in COVID-19 Patients: Case Series of Eight Patients in a Hemodialysis Unit. - Rind, Habib Ullah; Iftikhar, Nadia; Rehman, Fazal ur; Zarkoon, Abdul Kareem; Mohkam, Syed; Rehman, Gulalai; Baig, Umar; Khan, Moheudin; Khan, Ghulam Muhammad; Ataullah, Attaullah (Pakistan Journal of Kidney Diseases, 2021)
The Pandemic of COVID-19 has grasped the whole world and changed dramatically, together with our social, occupational and personal life with high mortality and morbidity with other consequences since December 2019 started from Wuhan and then declared pandemic in March. It has been observed to involve every organ of the body including skin. Various skin manifestations, but most cases reported were like urticarial rash, xanthemas, chickenpox-like vesicle, vasculitidic type, pressure sores, contact dermatitis and a single case was reported in china with skin darkening. The COVID-19 and cutaneous manifestations are recognized by physicians and dermatologist treating COVID-19. We have observed around eight cases of COVID -19 who had skin darkening in our center Baluchistan Institute of Nephrology and Urology Quetta, among these included were six dialysis technicians one chronic maintenance dialysis patient and a physician. We present the representative cases and discuss the skin manifestations of COVID-19.